PENGARUH TERPAAN SALES PROMOTION DAN INTENSITAS MELIHAT ONLINE CUSTOMER REVIEW PADA MEDIA SOSIAL TIKTOK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINTIFIC - Yoshita Rindha Anggraini; Muhammad Bayu Widagdo; Lintang Ratri Rahmiaji (Interaksi Online, 2023)
The continued increase in demand for beauty products in Indonesia makes many brand beauty began to intensively carry out marketing communication strategies, one of which is Skintific. With these conditions, this study aims to see the effect of exposure sales promotion and viewing intensity online customer review on social media TikTok on purchasing decisions for Skintific products in the city of Semarang. This study uses Advertising Exposure Theory and Buyer Information Environment Theory. Data collection used a questionnaire with a sample size of 100 respondents with the criteria of Semarang city residents who have purchased Skintific products at least once in the last 3 months and have an active TikTok social media account. Retrieval of data using non-probability sampling technique by purposive sampling method and processed using a simple linear regression analysis technique with the SPSS 23 program. From this study it was found that Sales Promotion Exposure has a positive and significant influence on the Purchasing Decision of Skintific Products. These results prove that the Advertising Exposure Theory relevant to this research. Likewise with the Intensity of Seeing Online Customer Review on TikTok Social Media which also has a significant and positive effect on Purchasing Decisions of Skintific Products. These results prove the existence of relevance to the Buyer Information Environment theory. Based on these results, it can be concluded that the higher the sales promotion exposure and intensity of seeing online